SPECIFIC FEATURES OF DEVELOPING CREATIVE THINKING IN PRIMARY SCHOOL CHILDREN - Hayitboyeva Zarina Otanazarovna (Modern American Journals, 2025)
This article explores the unique psychological and pedagogical features of developing creative thinking in primary school children. It examines the role of digital learning environments, age-related cognitive characteristics, and innovative teaching methods that stimulate imagination, problem-solving, and independent thinking. The study emphasizes the importance of interactive activities, project-based learning, and creativity-focused tasks in fostering flexible and original thought processes. Practical recommendations for teachers and school psychologists are provided to effectively support and enhance creative thinking skills in young learners.
Keywords: Creative thinking, primary school children, cognitive development, digital education, innovation, imagination, problem-solving, pedagogical approaches